Factors Affecting Unsuccessful Suicide Among Women Referred to Emergency Room of Ardabil City Hospital, Ardabil, Iran - Farzaneh, Esmaeil; Amani, Firouz; Sadeghi-Movahhed, Fariba; Mataei, Kaveh (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Background: Along with the complexity of social communications, the rate of suicide is increasing, and according to studies, women commit suicide more than men. Various factors affect the occurrence of this phenomenon. The purpose of this study was to determine the factors affecting unsuccessful suicide among women referring to the emergency room of the hospital of Ardabil City, Iran. Methods: This study was a descriptive cross-sectional study conducted on 236 women who had unsuccessful suicide. Questions were asked from patients with a checklist. This checklist has four parts. The first part relates to the patient’s personal information, and the second part relates to the patient’s previous history of mental, physical, and addiction problems. The third part asked about the causes of suicide and the fourth part related to the prior announcement. The collected data were analyzed by statistical methods in SPSS v. 18. Results: The Mean±SD age of the women was 27.66±9.95 years, and the majority was between 15 and 20 years old. About 64% of women were housewives, and 37.7% had undergraduate education. Also, 36% had a positive history of psychological diseases, and 30.9% had a history of suicide. The most common causes of suicide among women were emotional problems (91.9%), family and marriage conflict (81.8%), spouse’s disregard (50.4%), and economic issues (44.5%). Conclusion: The results showed that emotional problems and family and marital conflicts were common causes of suicide among women, and all women had at least one crucial reason for their suicide attempt.